Next Generation Sequencing in diagnosis of mitochondrial epilepsy (International Journal of Biology and Chemistry, 2021)
Epilepsy is a common manifestation of mitochondrial disorders, in addition mitochondrial oxidative stress may play an important role in epileptogenesis since it affects the excitability of neurons. Mitochondrial diseases are often difficult to diagnose unless the symptoms are clearly identified as a part of a specific mitochondrial mutation. The use of next-generation sequencing would lead to the rapid identification of genes associated with epilepsy syndromes. In this study, we evaluate the applicability of the NGS method for diagnosis of mitochondrial epilepsy by clinicians and laboratories in Kazakhstan. We performed complete mitochondrial genome sequencing on the Illumina MiSeq platform for 6 patients with epilepsy. Using the MITOMAP and HmtDB databases, we identified three pathogenic variants (MT-ND1 m.3697G> A, m.5628T> C and m.7547T> C) leading to the development of epilepsy, additionally we found 6 variable sites (m.5586C> T, m.10095C> T, 514_515delCA, 16180_16181delAA, C514.CACACA, A955. ACCCC), the clinic of which was not previously mentioned in the literature. Our preliminary study suggests that mitochondrial genes potentially play a role in the pathogenesis of epilepsy and mutations in these genes cause various forms of epilepsy. It is necessary to elucidate the main mechanisms and participation of variants of mtDNA haplogroups in the development of epilepsy to apply the NGS method in diagnosis of mitochondrial epilepsy.